FAKTOR PENENTU YANG MEMPENGARUHI PENDAPATAN PETANI JAGUNG DI DESA CEMBA KAB. ENREKANG - Tarawiru, Yasri; Nuryadin, Rusmin; T, Hasni (Program Studi Ekonomi Pembangunan Fakultas Ekonomi dan Bisnis Universitas Muhammadiyah Parepare, 2021)
Agriculture is the largest sector in almost every developing country's economy. This sector provides food for the majority of the population and provides employment. The structural transformation of the Indonesian economy towards a direction that industrialization does not automatically establish an agrarian atmosphere. This study aims to determine the factors that affect the income of corn farmers in Cemba Village and determine the dominant variables that affect the income of corn farmers in Cemba Village. This type of research is quantitative research. The data sources are taken from observations, interviews, and questionnaires. This study was 264 people. Determination of the sample in this study using the Slovin formula, namely 264 population into 73 respondents. The data analysis technique in this study used multiple linear regression analysis with the help of SPSS 23 software. The results of this study indicate that simultaneously the independent variables have a significant and significant effect. positively related to this. The dependent variable is the income of corn farmers. Partially, the variables of land area, cost of seeds, and price of output have a significant effect. While the cost of fertilizer and labor costs have no significant and negative effect on the income of corn farmers from the results of the R square (R3) regression value of 0.865%, then the remaining 14.4% is explained by other variables outside of the study.